2022
DOI: 10.3390/cells11030527
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Metabolomic Landscape of Right-Sided and Left-Sided Colorectal Cancer: Potential Preventive Biomarkers

Abstract: Colorectal cancer (CRC) is the third most common cancer worldwide. The incidence and mortality rates of CRC are significantly higher in Taiwan than in other developed countries. Genes involved in CRC tumorigenesis differ depending on whether the tumor occurs on the left or right side of the colon, and genomic analysis is a keystone in the study and treatment of CRC subtypes. However, few studies have focused on the genetic landscape of Taiwanese patients with CRC. This study comprehensively analyzed the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Right‐sided CRC has a higher mortality rate and worse prognosis than left‐sided CRC, and both genetic and metabolomic differences between these two sides have been reported. 58 , 59 , 60 Therefore, we evaluated the difference between the left and right colon on prediction accuracy. There was no significant difference between tumor locations even in the training and validation data (Figure S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Right‐sided CRC has a higher mortality rate and worse prognosis than left‐sided CRC, and both genetic and metabolomic differences between these two sides have been reported. 58 , 59 , 60 Therefore, we evaluated the difference between the left and right colon on prediction accuracy. There was no significant difference between tumor locations even in the training and validation data (Figure S7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A Dutch study including 10,878 patients with LACC indicated that old age (≥70 year), incomplete resection margin, and nodal positivity status were significantly associated with poor survival [ 4 ]. The site of colon cancer development is another key prognostic factor for LACC ( Figure 2 ) [ 55 , 56 , 57 , 58 ]. Differences in the embryonic origin divide the colon into left and right sides.…”
Section: Role Of Biomarkers In Lacc Treatmentmentioning
confidence: 99%
“…Colorectal cancer and its TME are remarkably heterogeneous, both anatomically and genetically ( 9 11 ). The tumor anatomical location, which is commonly described as left- or right-sided colorectal cancers, contributes to the heterogeneity ( 12 , 13 ). In addition, studies have revealed the genetic heterogenicity of colorectal cancers, as evidenced by concurrent high- and low-frequency mutations and transcription profile drift ( 10 , 14 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to anatomical heterogeneity, the right-sided intestine originates from embryonic midgut, while the left-sided large intestine originates from embryonic hindgut. This ontogenetic divergency may explain the disparity in gene expression profiles between the left- and right-sided colon, as well as colorectal cancers ( 13 ). Clinical data indicated that left-sided colorectal cancer has a better prognosis than right-sided cancers, and showed increased susceptibility to first-line FOLFIRI plus cetuximab therapy ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation